International consensus statement on the psychosocial and policy-related approaches to mental health awareness programmes in sport. Issue 1 (18th September 2019) - Breslin, Gavin; Smith, Andy; Donohue, Brad; Donnelly, Paul; Shannon, Stephen; Haughey, Tandy Jane; Vella, Stewart A; Swann, Christian; Cotterill, Stewart; Macintyre, Tadhg; Rogers, Tim; Leavey, Gerard
Abstract : Background: Research focused on mental health in sport has revealed a need to develop evidence-supported mental health practices that are sensitive to sport culture, particularly for non-elite athletes. A consensus statement was produced to assist effective mental health awareness in sport and guide programme implementation in this rapidly emerging field. Method: The AGREE Reporting Checklist 2016 was used in two international expert consultation meetings, followed by two online surveys. Experts from 10 countries and over 30 organisations contributed. Results: Six objectives were agreed: (1) to define mental health awareness and service implementation constructs for inclusion in programmes delivered in sporting environments; (2) to identify the need to develop and use valid measures that are developmentally appropriate for use in intervention studies with sporting populations, including measures of mental health that quantify symptom severity but also consider causal and mediating factors that go beyond pathology (ie, well-being and optimisation); (3) to provide guidance on the selection of appropriate models to inform intervention design, implementation and evaluation; (4) to determine minimal competencies of training for those involved in sport to support mental health, those experiencing mental illness and when to refer to mental health professionals; (5) to provide evidence-based guidance for selecting mental health awareness and implementation programmes in sport that acknowledge diversity and are quality assured; and (6) to identify the need for administrators, parents, officials, coaches, athletes and workers to establish important roles in the promotion of mental health in various sports settings. Conclusion: This article presents a consensus statement on recommended psychosocial and policy-related approaches to mental health awareness programmes in sport.